Azerbaijan Foreign Trade 2024: Statistical Analysis and Devaluation Expectations - Gubad Ibadoghlu (Turan, 2025)
In 2024, one of the most notable developments in the Azerbaijani economy that demands detailed analysis is the transformation of foreign trade statistics. This article provides an in-depth examination of Azerbaijan's foreign trade landscape in 2024, focusing on its dynamics, structure, and geographic composition. It evaluates emerging trends, highlights current and future challenges, and considers devaluation expectations alongside their short- and medium-term implications. For a comprehensive perspective, the analysis also includes a retrospective review of the past three years, emphasizing the post-COVID recovery period.
Keywords: 330; Azerbaijan; customs statistics; foreign trade turnover; export; import; trade balance; trade partner; goods; crude oil; natural gas; food products; currency; manat; devaluation